Guest

y = y 1 +y 2 = a [sin 2π (t/T – x/λ) + sin 2π (t/T + x/λ)] = a [2sin (2πt/T) cos (2πx/λ)] So, y = 2a cos (2πx/λ) sin (2πt/T) how was the second step in terms of COS arrived?

 

y = y1+y2

= a [sin 2π (t/T – x/λ) + sin 2π (t/T + x/λ)]

= a [2sin (2πt/T) cos  (2πx/λ)]

So, y = 2a cos (2πx/λ) sin (2πt/T)      

how was the second step in terms of COS arrived?

 

Grade:11

1 Answers

Vikas TU
14149 Points
2 years ago
Dear student 
It is derived by using the formula 
SinA + Sin B = 2 Sin(A+B)/2 * Cos(A-B)/2 
Hope this will help 
Good Luck 
Cheers 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free